Highly sulfur-tolerant Pd composite membranes with a protective layer of MoS2/γ-alumina. Issue 19 (2nd May 2017) - Chen, Bingbing; Xu, Tianying; Li, Hui; Bao, Feng; Yu, Jiafeng; Li, Xinzhong; Xu, Hengyong
Abstract : Sulfur-tolerant Pd-based composite membranes were produced by coating a thin layer of MoS2 /γ-alumina on the membrane surface. Abstract : Sulfur-tolerant Pd-based composite membranes were produced by coating a thin layer of MoS2 /γ-alumina on the membrane surface. This layer acted as an "armor" to prevent H2 S from directly contacting the Pd membrane surface by preferentially adsorbing and decomposing the H2 S.